SPESIASI DAN BIOAVAILABILITAS LOGAM BERAT TIMBAL (Pb) DAN TEMBAGA (Cu) DALAM SEDIMEN SUNGAI TUKAD BADUNG - Nanik Wijayanti; I Made Siaka; Ida Ayu Gede Widihati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
A study of speciation and bioavailability of heavy metals, Pb and Cu in sediments of Tukad Badung river with sequential extraction method has been carried out. This study aimed to determine the levels of bioavailability of both Pb and Cu heavy metals. The determination of total heavy metal contents was performed by digestion technique with the use of a mixture of HNO3 and HCl (3:1) in ultrasonic bath for 45 minutes at 60oC followed by heating on a hotplate for 45 minutes at 140oC. The mesurement of total heavy metals and heavy metal species was established with the use of Atomic Absorption Spectrophotometer (AAS) with calibration curve method. Concentration of total Pb and Cu in the sediments of Tukad Badung river ranged from 4.2669 to 27.9171 mg/kg and 20.5240 to 69.3782 mg/kg respectively. The speciation of Pb obtained in carbonate fraction of the EFLE (easly, freely, leachable and exchangable) fractions ranged from 1.5952-11.6315 mg/kg, in Fe/Mn oxide fraction ranged from 0.4001 to 6.7680 mg/kg, in organic/sulfide fraction ranged from 0.8759 to 13.6600 mg/kg, and in the silicate fraction (resistant) ranged between Nd (not detected) to 4.6598 mg/kg. The level of bioavailability Pb in sediments ranged from 9 to70% while the non-bioavailability levels ranged from 0 to 30%. Carbonate fraction (EFLE) of Cu ranged between Nd (not detected) to 6.3527 mg/kg. The fraction of Fe/Mn oxides ranged from 0.7331 to 9.9033 mg/kg, organic sulfide fraction ranged from 8.1790 to 41.5756 mg/kg, and the silicate fraction was foud vary between 7.5138 and 21.0200 mg/kg. The level of Cu bioavailability in sediments ranged from Nd (not detectable) to 18%, while the level of non bioavailability ranged from 15 to 44%.